Optimising Sentinel-2 MSI spatial resolution for estimating foliar nitrogen concentration in miombo woodlands. Issue 1 (2nd January 2023) - Mutowo, Godfrey; Mutanga, Onisimo; Masocha, Mhosisi
ABSTRACT: The landscape-level estimation of nitrogen will constitute a significant input in global change models. High resolution broadband satellite technology is a promising solution to the limitation of spatial coverage. This study sought to identify an optimal spatial resolution for estimating foliar nitrogen in dry miombo woodlands. The contrast texture measure, calculated at increasing window size on Sentinel-2 imagery, was related to field measured nitrogen via random forest regression models. Our results show that the optimum size for estimating nitrogen is 50m. This result is significant in understanding the scale at which dynamics in foliar nitrogen concentration can be remotely measured.